Front Cover: Direct coupling of size exclusion chromatography and mass spectrometry for the characterization of complex monoclonal antibody products. Issue 12 (27th June 2022) - Murisier, Amarande; Andrie, Marie; Fekete, Szabolcs; Lauber, Matthew; D'Atri, Valentina; Iwan, Katharina; Guillarme, Davy
Abstract : DOI: 10.1002/jssc.202200075 The SEC mobile phase was exclusively composed of 50 mM ammonium acetate in water, while a specially designed bioinert SEC column was employed, as highlighted in the central part of the picture. This column includes a novel hardware surface where column frits and metallic column walls were treated to have prototype hydrophilically modified hybrid organicinorganic silica surfaces. This new material instead of stainless steel strongly reduce non‐desired hydrophobic and electrostatic interaction under SEC conditions with volatile mobile phase. Thus, an improvement of peak tailing, band broadening and above all recovery of mAb products was noticed with this new column hardware compared to regular SEC column, as illustrated in the left panel of the picture. Finally, the direct SEC‐MS analysis was successfully applied to characterize low molecular weight species (fragments) and high molecular weight species (such as dimer) contained in complex bispecific mAb products with mass spectrometry, as shown in the right part of the picture.